O planejamento metropolitano e a extensão universitária: um estudo dos Lumes - Caroline Cristiane Rocha (2023)
This research discusses how university extension has contributed to enlarge the participation and mobilization in urban planning. Taking the Lumes program as a case (Lugares de Urbanidade Metropolitana), one of the developments of the Plano Diretor de Desenvolvimento Integrado da Região Metropolitana de Belo Horizonte (PDDI-RMBH), a record of experiences already carried out is developed – by extensionist disciplines at the Escola de Arquitetura and the Faculdade de Economia, both at the Universidade Federal de Minas Gerais. The effort to resume these experiences, through the analysis of academic production on the Lumes and through the collection of reports from former students and people who became partners in extensionist actions, leads to the search for another urban planning practice. The investigation advances to think about other design tools that can promote the activation of spaces and the articulation of the agents inserted there, strengthening the role of local decisions in the metropolitan scale. Finally, the follow-up during four semesters the classes LUMEs – Planejamento e Cidadania na RMBH made it possible to understand (and participate) in the proposals for collaborative planning actions, carried out by the students based on the community mobilization of partners in the municipalities of Matozinhos and Nova União (Minas Gerais). It’s expected to point out possible ways for the continuity of the Lumes, which, in addition to an innovative extensionista experience, proves to be an urban planning tool capable of encouraging social participation, highlighting the scale of everyday life as the appropriate scale for us to dare to build fairer urban spaces.